Developing distributed simulation applications in a cluster/grid environment - Chia Shu Ting. (2011)
Simulation is a cost saving method to solving complex problems in various areas such as production, science and engineering, health care and etc. Distributed simulation would allow the interoperability and reusability of simulation components at different geographically locations.